2009
DOI: 10.1111/j.1539-6924.2008.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

“Trust me, I'm a Scientist (Not a Developer)”: Perceived Expertise and Motives as Predictors of Trust in Assessment of Risk from Contaminated Land

Abstract: Previous authors have argued that trust may be based on the extent to which risk communicators are seen as good at discriminating safety from danger, are unbiased in their assessments, and share their audience's values. Residents of two English urban regions rated their trust in six potential sources of information about the risk of contaminated land in their neighborhood (independent scientists; local council property developers; residents' groups; friends and family; local media), and how expert, open, accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 19 publications
10
63
0
Order By: Relevance
“…Studies have demonstrated the importance of trust in the acceptance of information about risk (e.g. Haynes et al 2008;Eiser et al 2008), but it is likely that there is a level of reciprocity: those who give information have to trust those receiving it to respond accordingly.…”
Section: Understanding Discrepanciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated the importance of trust in the acceptance of information about risk (e.g. Haynes et al 2008;Eiser et al 2008), but it is likely that there is a level of reciprocity: those who give information have to trust those receiving it to respond accordingly.…”
Section: Understanding Discrepanciesmentioning
confidence: 99%
“…Haynes et al 2008;Eiser et al 2008), and are increasingly expected to take part in the risk communication process. Yet the L' Aquila trial in Italy and the conviction of scientists in 2012 for "having given out falsely reassuring information to members of the public" suggests that involvement of scientists in risk communication can be problematic (Alexander 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on eta squared, both effects can be characterised as small to medium-sized (Hedrick, Bickman, & Rog, 1993). This latter finding is consistent with the literature on trust: the lower the perceived expertise of a source, the lower the trust in that source (Eiser, Stafford, Henneberry, & Catney, 2009;Garretson, & Niedrich, 2004), and the lower the trust, the higher the risk perception (Siegrist & Cvetkovich, 2000;Siegrist, 2000;Viklund, 2003). It is also consistent with finding that individuals perceive anonymous online authors as untrustworthy (Rutsaert, Pieniak, Regan, McConnon, & Verbeke, 2013b).…”
Section: Discussionsupporting
confidence: 81%
“…The dynamics are probably more complex, as volcanologists are only one of the many stakeholders (Macías Medrano 2005). Nevertheless, after friends and relatives, scientists are found to be the most trusted source of volcanological information, while government authorities are generally distrusted (Barberi et al 2008;Gavilanes-Ruíz et al 2009;Haynes et al 2008a;Eiser et al 2009). In recent years, some volcanologists feel that their work should be guided by its social relevance (mode 2 research), rather than being purely determined by traditional, research-based science (mode 1 research, Gibbons et al 1994) (Johnston et al 1999;Cronin et al 2004a, b;Gregg et al 2004;Barberi et al 2008;Haynes et al 2008a, b;Donovan et al 2011Donovan et al , 2012aBowman and White 2012;Donovan and Oppenheimer 2012;Johnston 2012).…”
Section: Introductionmentioning
confidence: 99%